As trocas interpessoais na Internet: privacidade e sociabilidade na era da cibercultura - Rocha, Aline Maria Matos (2010)
To analyze the phenomenon of exposure of privacy and sociability forms provided by Internet is the issue of this research. This is a study of the reasons that make a lot of people post their personal characteristics on Internet. It is a qualitative research with an exploratory and comprehensive nature. Its universe is composed by individuals who participate of a virtual and social relationship networking site, orkut, that live in Fortaleza-CE . Through a virtual ethnography; it was possible to analyze the spaces of socialization mediated by computer , keeping in mind that Internet is, at the same time, context and cultural articraft. The study of the downsizing of public and private spheres made possible to verify that the territory of inner life gradually assumed importance when we saw accelerating the processes of individualization. A growing burden of concerns around issues of private sphere and inner conflicts have brought significant changes regarding the design of the public. In the fluid environment of Internet, theses concepts assumed different forms, since in that instance the areas of public and private become out from rigid and polarized orders. The publication of personal networks in virtual relationship arises as a mechanism which highlights the subjective and the objective investment of the subject itself. The network individualism emerges as a result of the personalization of social relations, carried around the construction of links focusing on common interests. The nature of the sociability exerced through this environment technically mediated, places itself at the service of flexible behaviors and become built on a base of afinity ties. The values propagated by the actual and technological culture belong to a more present reality inside the social body and the discussions that will take place during theis study aimed to contribute to empirical studies that will seek for new meanings wich give other significances to the society in which we live.